Hieracia balcanica XVI. Taxonomic and nomenclatural notes on Hieracium rotundatum and H. transylvanicum (Asteraceae) - Szeląg, Zbigniew (Phytotaxa, 2018)
Hieracium rotundatum Kit. ex Schult. and H. transylvanicum Heuff., two species of H. sect. Transsilvanica (Zahn) Schljakov, have been confused under the older name H. rotundatum in the most important European monographs. The original specimen of H. rotundatum stored at BP is recognized as the holotype and re-identified as a representative of the H. praecurrens aggregate. Hieracium transylvanicum is lectotypified using a specimen also stored at the Hungarian Museum of Natural History in Budapest (BP). The original spelling of the species epithet of H. transylvanicum is clarified.